Roles of Wnt signaling in bone formation and resorption - Yasuhiro Kobayashi; Kazuhiro Maeda; Naoyuki Takahashi (Elsevier, 2008)
Wnt proteins (Wnts) are palmitoylated and glycosylated ligands that play a central role in the early development of organs and tissues. The discovery that loss-of-function mutations in low density lipoprotein receptor-related protein 5 (LRP5), a Wnt co-receptor, led to low bone mass in humans revealed the possible role of Wnt signaling in the regulation of bone remodeling. Many findings obtained from detailed analyses of mice having mutations of Wnt signaling molecules have confirmed that Wnt signaling has potential roles in bone remodeling in both physiological and pathological conditions. There are two pathways of Wnt signaling: β-catenin-dependent canonical and -independent non-canonical pathways. Wnts act on osteoblast precursor cells and promote their differentiation into mature osteoblasts through the β-catenin-dependent canonical pathway. In addition, Wnts suppress bone resorption by regulating the receptor activator of NF-κB ligand (RANKL)/osteoprotegerin (OPG) ratio through the same pathway in mature osteoblasts. In contrast, recent studies have shown that the activation of the β-catenin-independent non-canonical pathway enhances the RANKL-induced osteoclast formation in mouse macrophage cultures. These results indicate that Wnt-mediated signals are involved in several aspects of bone formation and bone resorption. This review will summarize the current knowledge of the roles of Wnt signaling in bone formation and resorption.